Cardiorespiratory Fitness, Physical Activity, Sedentary Behavior, and Circulating White Blood Cells in Us Youth - Garcia-Hermoso, A (Blackwell Munksgaard, 2021)
The white blood cell (WBC) provides a clue to the presence of illness. Cardiorespiratory fitness (CRF) and physical activity levels are negatively associated with circulating total WBC counts in adults. To date, only a scarce number of studies have investigated these associations among youths. The aim was to elucidate the relationship between CRF and accelerometer-assessed physical activity and sedentary behavior with WBC counts and subfraction concentrations of particular WBC (neutrophils, lymphocytes, monocytes, basophils, and eosinophils) in a large representative national sample of US children and adolescents. Participants accumulating 60 min/day or more of moderate-to-vigorous physical activity (MVPA) were considered active or inactive otherwise. Participants were also categorized into low, average, and high CRF level. The final sample consisted of 1623 children and adolescents (11.9 years old) from 2003 to 2006 cycle and 2624 (14.5 years old) from 1999 to 2004 cycle. CRF was inversely associated with total WBC and segmented neutrophils concentration in both sexes, and MVPA only in boys. Further, active children and adolescents had higher odds of a normal range of WBC count in boys (Odds Ratio [OR] = 1.41 95% CI, 1.02 to 2.34) and girls (OR = 3.52 95% CI, 1.01 to 12.23). In conclusion, our observations indicate that interventions targeting CRF and MVPA could strength the immune system of children and adolescents. © 2020 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd